Mathematical modeling and experimental study of heat and mass transfer in cupcake baking using an air fryer - Soumia, Boussaha; Djamel, Haddad; Afaf, Djaraoui; Salima, Baississe (Journal of Food Technology Research, 2025)
Baking involves simultaneous heat and mass transfer, alongside physical and chemical transformations that determine product quality. While conventional baking has been extensively modeled, air fryer baking remains underexplored, despite its growing popularity as a healthier alternative. This study aims to develop and experimentally validate a mathematical model describing heat and mass transfer during cupcake baking in an air fryer. The model incorporates forced convection, conduction, thermal radiation, gas release, and porosity evolution. It also integrates the simulation of the cooking value (CV), a parameter analogous to the sterilization value, to standardize heat treatment assessment. To validate the model, experimental baking trials were conducted, with color changes used as a key quality indicator. The results showed strong agreement between simulated and experimental data, confirming the model’s reliability in predicting temperature profiles, porosity, moisture loss, gas generation, and browning kinetics. Color measurements further validated the model, achieving a high coefficient of determination (R²=0.996). These findings demonstrate the air fryer’s efficiency in reducing baking time while ensuring optimal quality. The model provides a valuable framework for optimizing heat and mass transfer in modern baking and can be extended to other processes involving phase transitions and volume changes, such as drying and extrusion cooking.